Rational approach towards enhancing solar water splitting: a case study of Au-RGO/N-RGO-TiO2 - Bharad, Pradnya A.; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Nanoscale, 2015)
A rational approach was employed to enhance the solar water splitting (SWS) efficiency by systematically combining various important factors that helps to increase the photocatalytic activity. The rational approach includes four important parameters, namely, charge generation through simulated sunlight absorption, charge separation and diffusion, charge utilization through redox reaction, and the electronic integration of all of the above three factors. The complexity of the TiO2 based catalyst and its SWS activity was increased systematically by adding reduced graphene oxide (RGO) or N-doped RGO and/or nanogold. Au-N-RGO-TiO2 shows the maximum apparent quantum yield (AQY) of 2.46% with a H-2 yield (525 mu mol g(-1) h(-1)) from aqueous methanol, and overall water splitting activity (22 mu mol g(-1) h(-1); AQY = 0.1%) without any sacrificial agent under one sun conditions. This exercise helps to understand the factors which help to enhance the SWS activity. Activity enhancement was observed when there is synergy among the components, especially the simulated sunlight absorption (or one sun conditions), charge separation/conduction and charge utilization. Electronic integration among the components provides the synergy for efficient solar light harvesting. In our opinion, the above synergy helps to increase the overall utilization of charge carriers towards the higher activity.

Is there any real effect of low dimensional morphologies towards light harvesting? a case study of Au-rGO-TiO2 nanocomposites - Melvin, Ambrose A.; Bharad, Pradnya A.; Illath, Kavya; Lawrence, Meenu P.; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Nanotube and nanosheet morphologies have been celebrated for their electron transport properties. Present work has been explored to exploit the same by combining 1D TiO2 nanotube (1D-TN) with 2D reduced graphene oxide (rGO) along with nano gold for visible light sensitization for photocatalytic H2 generation under one sun condition and visible light (λ≥ 400 nm). Vertical and horizontal electron transport in 1D-TN and rGO, respectively, is combined with the visible light absorption capability of Au nanoparticle. H2 yield (HY) varies between 100 and 655 µmol/g.h with an apparent quantum yield between 0.45 and 3.2 %, respectively, depending on Au/rGO/1D-TN preparation method and reaction conditions. It has been demonstrated that interfacial contact between rGO/1D-TN and Au is crucial for high photocatalytic HY. Preparation method influences charge utilization, and hence HY, to a large extent. Nonetheless, the maximum HY reported in the present work is just comparable to HY reported in literature with the most commonly found spherical morphology, and this leads to a question of, is there any real influence of 1D and/or 2D materials, particularly, towards light harvesting applications?

CuOx-TiO2 composites: electronically integrated nanocomposites for solar hydrogen generation - Bharad, Pradnya A.; Nikam, Arun, V.; Thomas, Femi; Gopinath, Chinnakonda S. (ChemistrySelect, 2018)
CuOx-TiO2 (CT) composites were prepared by different methods (impregnation, microwave and photodeposition methods) and evaluated for solar water splitting (SWS) with aqueous methanol. CT composites prepared by three different methods were characterized by relevant methods to understand the correlation between synthesis method and activity, and the mechanism of water splitting. A comparison of photocatalytic activity of CT composite materials indicates that the photocatalyst prepared by photodeposition method shows significantly improved activity for hydrogen production from aqueous methanol as well as with water (overall water splitting) under one sun conditions. Cu is present in Cu/Cu+1 form in photodeposition method prepared CT, which is more effective and helpful for solar light absorption as well as charge carrier separation due to the formation of bulk p-n (Cu2O-TiO2) heterojunctions. However, CuO formation seems to decrease the activity with other preparation methods.

Why the thin film form of a photocatalyst is better than the particulate form for direct solar-to-hydrogen conversion: a poor man's approach - Nalajala, Naresh; Patra, Kshirodra Kumar; Bharad, Pradnya A.; Gopinath, Chinnakonda S. (RSC Advances, 2019)
We demonstrated an easy method to improve the efficiency of photocatalysts by an order of magnitude by maximizing light absorption and charge carrier diffusion. Degussa titania (P25) and Pd/P25 composite photocatalyst thin films coated over regular glass plates were prepared and evaluated for solar hydrogen production in direct sunlight with aqueous methanol. It is worth noting that only UV light present in direct sunlight (similar to 4%) was absorbed by the catalysts. The hydrogen production activities of catalysts were compared for thin film and particulate forms at 1 and 25 mg levels. The hydrogen yield values suggested that 1 mg thin film form of Pd/P25 provided 11-12 times higher activity than 25 mg powder form. Comparable light absorption throughout the entire thickness of photocatalyst device and better contact of nanostructures that enabled the charge diffusion and charge utilization at redox sites are the reasons for high efficiency. While solar cells require charge carriers to diffuse through long distances of microns, they are utilized locally in an ensemble of particles (of nanometres) for hydrogen generation in photocatalyst thin films; this concept was used effectively in the present work.